2023
DOI: 10.1111/jpm.12928
|View full text |Cite
|
Sign up to set email alerts
|

Suicide prevention: What does the evidence show for the effectiveness of safety planning for children and young people? – A systematic scoping review

Abstract: Accessible SummaryWhat is known on the subject? Suicide prevention is an international healthcare priority. There is an urgent need to use approaches that are helpful and follow research evidence. Safety planning is now widely used in suicide prevention; however, it was developed for use with adults, and little is known about its effectiveness for children/young people. What the paper adds to existing knowledge? This systematic scoping review brings together all research evidence since 2008 that reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The involvement of parents is critical when working with suicidal CYP but, whilst parents/carers have a crucial role in safety planning they are often left out of the process (Berk, 2019). Although our recent scoping review found that that no safety plans designed for use by parents of suicidal children existed, we were able to identify six elements to support safety planning by parents for CYP (Abbott-Smith et al, 2023). Findings from the scoping review and these F I G U R E 1 This is the Lothian Safekeeping Plan and the Lothian Safety Plan.…”
Section: The Lothian Safekeeping Plan © For Use With Parentsmentioning
confidence: 86%
See 2 more Smart Citations
“…The involvement of parents is critical when working with suicidal CYP but, whilst parents/carers have a crucial role in safety planning they are often left out of the process (Berk, 2019). Although our recent scoping review found that that no safety plans designed for use by parents of suicidal children existed, we were able to identify six elements to support safety planning by parents for CYP (Abbott-Smith et al, 2023). Findings from the scoping review and these F I G U R E 1 This is the Lothian Safekeeping Plan and the Lothian Safety Plan.…”
Section: The Lothian Safekeeping Plan © For Use With Parentsmentioning
confidence: 86%
“…However, until recently safety plans for parents did not exist (Berk, 2019). A recent systematic scoping review (Abbott-Smith et al, 2023) revealed other studies within this field of safety planning with CYP. Asarnow et al (2015) and Berk (2019) identified that although some brief interventions included parents, there remained a need to include them in a collaborative manner within safety planning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Safety planning has shown potential to decrease suicidal behaviors in adults [81][82][83] and may help reduce the risk of suicide in youth. 84 Components of safety planning include: recognizing warning signs of an impending crisis; employing internal coping strategies; utilizing social contacts as a means of distraction from suicidal thoughts; contacting family members or friends who may help to resolve the crisis; contacting MBH professionals. 82,85 Tools such as the Stanley-Brown Safety Plan can assist EPs with discharge planning.…”
Section: Safety Planningmentioning
confidence: 99%
“…Psychotherapy may be delivered face to face, but web-based programs are increasing in popularity [15]. Usually, clinicians also work with young people and their caregiver/s to develop and implement a safety or management plan, which aims to keep a young person safe as other interventions are being implemented [16,17].…”
Section: Interventions To Prevent Suicidementioning
confidence: 99%